Inside the gate : Sigrid Undset's life at Bjerkebæk - Skille, Nan Bentzen (University of Minnesota Press, 2018)
"Inside the Gate offers readers a rare glimpse into Sigrid Undset's life at her home, Bjerkebæk now a museum and national landmark in Lillehammer, Norway. Drawing on a wealth of historical documents, Nan Bentzen Skille's lively narrative presents an intimate portrait of the Nobel Prize winner's intense emotional life and creative endeavors, with Bjerkebæk at the center of it all"--